Transferencias e inhibición retroactiva con bilingues - Young, Robert K. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Mexican American bilingual in Texas is an interesting subject for research. The present study attempts to answer some questions concerning learning and retention in connection with first and second language and association. Three studies were conducted presenting subjects two related words of pair of nouns, first in English and then Spanish and vice-versa. The subjects of the first experiment included 48 high school students that could speak and read in English but could only speak and understand English. The second experiment included 40 Spanish English bilingual college students whose dominant language was English but could also read Spanish. The third experiment was carried out with a group of students, al of them bilinguals but half of them had English as their dominant language and the other half had Spanish. The main conclusion drawn from the experiments was that the language of a bilingual are not two independent set of responses and that the association formed in one language are strongly influence by the associations in the other. The implications of this conclusion towards the elementary programs for bilingual children are obvious.